2022
DOI: 10.1371/journal.pone.0274963
|View full text |Cite
|
Sign up to set email alerts
|

Examining adherence to oral anticancer medications through a human factors engineering framework: Protocol for a scoping review

Abstract: Background The number of oral anticancer medications has increased over the past few decades, opening new possibilities in cancer care and improving convenience for patients and caregivers. However, adherence levels continue to be suboptimal, potentially jeopardizing therapeutic benefits. Poor adherence levels may indicate gaps in current strategies and interventions aimed at enhancing medication adherence and the extent to which they address the complex and multi-faceted medication management needs of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…17,18 A novel approach to examining adherence to oral chemotherapy is through the viewpoint of human factors engineering with emphasis on the interactions between the caregivers' tasks and the tools and technology available to them. 19 The framework is adapted from the patient work system model, 20 with the inclusion of organization, social-cultural, and physical-spatial contexts, which then translates into care processes (including administering, refilling, organizing, and tracking medications), which impact patient outcomes including adherence. Through a software tool to streamline the creation of chemotherapy calendars that offer a printable version desired by oncologists, this could help in shifting the paradigm for why we create these toward envisioning it as a tool for enhancing care at home for our patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 A novel approach to examining adherence to oral chemotherapy is through the viewpoint of human factors engineering with emphasis on the interactions between the caregivers' tasks and the tools and technology available to them. 19 The framework is adapted from the patient work system model, 20 with the inclusion of organization, social-cultural, and physical-spatial contexts, which then translates into care processes (including administering, refilling, organizing, and tracking medications), which impact patient outcomes including adherence. Through a software tool to streamline the creation of chemotherapy calendars that offer a printable version desired by oncologists, this could help in shifting the paradigm for why we create these toward envisioning it as a tool for enhancing care at home for our patient population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, with the shift toward trying to include patient‐centered outcomes into oncologic clinical care, it was found that barriers tended to be organizational, with time constraints and insufficient staff as key factors 17,18 . A novel approach to examining adherence to oral chemotherapy is through the viewpoint of human factors engineering with emphasis on the interactions between the caregivers' tasks and the tools and technology available to them 19 . The framework is adapted from the patient work system model, 20 with the inclusion of organization, social‐cultural, and physical‐spatial contexts, which then translates into care processes (including administering, refilling, organizing, and tracking medications), which impact patient outcomes including adherence.…”
Section: Discussionmentioning
confidence: 99%